2002
DOI: 10.1046/j.1463-1326.2002.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum homocysteine concentration is related to diabetes mellitus, but not to coronary heart disease, in Saudi Arabians

Abstract: In the Saudi Arabian population, serum HCYS is not a risk factor for CHD, but is lower in patients with DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…In all groups, there was a strong negative association between the HCYS level and a family history of diabetes as well as between HCYS and glucose levels. This reaffirms our previous findings that serum HCYS is lower in Saudi patients with diabetes mellitus because HCYS levels of subjects who are genetically predisposed to develop diabetes also have lower HCYS levels [35].…”
Section: Discussionsupporting
confidence: 91%
“…In all groups, there was a strong negative association between the HCYS level and a family history of diabetes as well as between HCYS and glucose levels. This reaffirms our previous findings that serum HCYS is lower in Saudi patients with diabetes mellitus because HCYS levels of subjects who are genetically predisposed to develop diabetes also have lower HCYS levels [35].…”
Section: Discussionsupporting
confidence: 91%
“…The study by Al-Nozha et al (2002) assessed the level of homocysteine, the independent vascular risk factor, and found that it is lower in Saudi diabetic patients, 53 in contrast to the study by Ajabnoor et al 54 Interestingly, Ajabnoor et al showed a linear relationship between LDL and homocysteine, an observation documented before in young menstruating Caucasian females. 55 More data is needed to resolve this disparity.…”
Section: Specific Diabetes Syndromesmentioning
confidence: 92%
“…Five studies have related hyperhomocysteinemia specifically to coronary heart disease in diabetes. 11,41,54,77,78 Smulders et al found a higher plasma homocysteine concentration in subjects with than in those without coronary artery disease (13.0 vs. 10.0 µmol/L, p = 0.02). 11 In a coronary angiography study by Okada et al, there was a strong correlation between the extent of coronary abnormalities and plasma homocysteine level in 46 patients who had diabetes (r = 0.388, p = 0.011), while this relationship was weaker and did not reach significance (r = 0.185, p = 0.068) in 99 subjects without diabetes.…”
Section: Figmentioning
confidence: 96%
“…Some authors have reported higher homocysteine levels in diabetic patients, 15,16,[41][42][43][44][45][46] while others have found similar 14,45,[47][48][49][50] or even lower levels. 35,[51][52][53][54][55][56] These discrepancies may be due mainly to the fact that most studies did not account for folate status and renal function, the two most important determinants of plasma homocysteine level. Correction for renal function is important, because even small changes in glomerular filtration rate have a significant impact on plasma homocysteine level.…”
Section: Determinants Of Plasma Homocysteine Concentrationmentioning
confidence: 99%
See 1 more Smart Citation